One Weapon, Three Manners: Case-based Discussion and Evaluation on Manner of Death - Rahul Kaushik; Jitender Kumar Jakhar; Sunil Kumar Dahiya; Kuldeep Kumar (Journal of Indian Academy of Forensic Medicine, 2026)
The forensic pathologist plays a critical role in determining the cause and contributing circumstances of death through medicolegal autopsy. Determination of the manner of death requires correlation of autopsy findings with scene investigation, weapon characteristics, and investigative inputs. Sharp-force injuries may result from accidental, suicidal, or homicidal circumstances, and wound morphology alone cannot establish the manner of death. This article presents three cases involving similar sharp-force mechanisms but differing manners of death and evaluates them using structured medicolegal reasoning based on scene findings, injury characteristics, and autopsy correlation. The cases demonstrate that the same broad class of weapon or injury mechanism may be associated with different manners of death. Accurate determination therefore requires a multidisciplinary, evidence-based approach integrating autopsy findings with scene investigation and other investigative information. While the forensic pathologist provides objective interpretation of injuries and cause of death, the final classification of manner of death depends on the overall medicolegal and legal assessment.